2018
DOI: 10.1038/s41370-018-0074-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the relationship between residential orchard density and dimethyl organophosphate pesticide residues in house dust

Abstract: Reducing residential pesticide exposure requires identification of exposure pathways. mCompared to the agriculture worker ‘take-home’ and residential use pathways, evidence of the ‘drift’ pathway to pesticide exposure has been inconsistent.Questionnaire data from individuals (n=99) and dust samples (n=418) from households across three growing seasons in 2011 were from the For Healthy Kids! study. Summed dimethyl organophosphate pesticide (OP) (Azinphos-Methyl, Phosmet, and Malathion) concentrations were quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…As presented in Table 4, 12 (31%) studies investigated the take-home pathway by measuring pesticides or pesticide metabolites in dust collected from agricultural workers’ homes and vehicles. Supporting the take-home pathway, two recent studies conducted in the U.S. Northwest found that pesticide residues in house dust may increase in relation to the number of residents working in agriculture [44,45]. In another study, Thompson et al (2008) collected dust from 210 farmworker homes and 204 farmworker vehicles [21].…”
Section: Resultsmentioning
confidence: 99%
“…As presented in Table 4, 12 (31%) studies investigated the take-home pathway by measuring pesticides or pesticide metabolites in dust collected from agricultural workers’ homes and vehicles. Supporting the take-home pathway, two recent studies conducted in the U.S. Northwest found that pesticide residues in house dust may increase in relation to the number of residents working in agriculture [44,45]. In another study, Thompson et al (2008) collected dust from 210 farmworker homes and 204 farmworker vehicles [21].…”
Section: Resultsmentioning
confidence: 99%
“…Among these studies, one also found an association between the distance to the closest crop field and herbicide exposure; however, distance alone accounted for less of the variance than crop acreage (Ward et al, 2006). One very good quality study found no association between surface area of orchards and residential concentrations of pesticides (Plascak et al, 2019). One medium quality study showed no association between the number of fields in the vicinity and urinary DAPs levels (Royster et al, 2002).…”
Section: Crop Acreage In One or Several Buffers Around The Homementioning
confidence: 99%
“…A solution to this, is using a bespoke clean doormat for the study period. By doing so, the sample taken from the doormat reflects solely currently used pesticides (Plascak et al, 2019). Only a limited number of studies have compared different dust matrixes (Lu et al, 2000;Moschet et al, 2018;Rostkowski et al, 2019;Dubocq et al, 2021) and few have looked into determinants of occurrence and concentrations of pesticides in indoor dust (Gunier et al, 2011, Deziel et al, 2019.…”
Section: Dust From Doormat and Vacuumingcurrent And Historical Pestic...mentioning
confidence: 99%